Effects of perioperative blood transfusion in gastric cancer patients undergoing gastrectomy: A systematic review and meta-analysis - Wang, Wanqing; Zhao, Lulu; Niu, Penghui; Zhang, Xiaojie; Luan, Xiaoyi; Zhao, Dongbing; Chen, Yingtai (Frontiers in Surgery, 2023)
Abstract Background: The short-term and long-term effects of perioperative blood transfusion (PBT) on patients with gastric cancer are still intriguing. This systematic review and meta-analysis aimed to investigate the effects of blood transfusion on clinical outcomes in patients with gastric cancer undergoing gastrectomy. Methods: We searched PubMed, Web of Science, Embase, and The Cochrane Library on December 31th 2021. The main outcomes were overall survival (OS), disease-free survival (DFS), disease-specific survival (DFS), and postoperative complications. A fixed or random-effects model was used to calculate the hazard ratio (HR) with 95% confidence intervals (CIs). Results: Fifty-one studies with a total of 41864 patients were included for this review and meta-analysis. Compared with patients who did not receive blood transfusions (NPBT), PBT was associated with worse 5-year OS (HR=2.39 [95%CI: 2.00, 2.84]; p<0.001; Multivariate HR=1.43 [95%CI: 1.24, 1.63]; p<0. 001), worse 5-year DFS (HR = 2.26 [95%CI: 1.68, 3.05]; p<0.001; Multivariate HR=1.45 [95%CI: 1.16, 1.82]; p<0. 001), and worse 5-year DSS (HR = 2. 23 [95%CI: 1.35, 3.70]; p<0.001; Multivariate HR=1.24 [95%CI: 0.96, 1.60]; p<0.001). Moreover, The PBT group showed a higher incidence of postoperative complications (OR=2.30 [95%CI:1.78, 2. 97]; p<0.001) than that in the NPBT group, especially grade Ⅲ-Ⅴ complications, according to the Clavien-Dindo classification. (OR=2.50 [95%CI:1.71, 3.63]; p<0.001). Conclusion: In patients who underwent gastrectomy, PBT was associated with negative survival effects (OS, DFS, DSS) and a higher incidence of perioperative complications. However, more research was expected to further explore the impact of PBT. Meanwhile, strict blood transfusion management should be implemented to minimize the use of PBT.